(untitled) - Sanders, Betsy (Amsterdam, 1995)
This program will help you develop exceptional customer service that puts your organization above your competition. Inspiring Fabled Service helps you assess your needs and select activities to improve weak areas in your current customer service.
Keywords: Customer services |x Management,Dịch vụ khách hàng; Quản lý